Improving the detection capability and efficiency of SARS-CoV-2 RNA specimens by the specimen turn-around process with multi-department cooperation - Liu, Chenggui; Shen, Wei; Xie, Huiqiong; Li, Ying; Cui, Rong; Wu, Rongcheng; Xiao, Li; Li, Jing; Guo, Yanjun; Liao, Yi; Zhao, Chonghui; Xu, Yunfei; et al. (Frontiers in Public Health, 2024)
Objective: Improving the detection capability and efficiency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA specimens is very important for prevention and control the outbreak of Coronavirus disease 2019 . In this study, we evaluated the detection capability and efficiency of two outbreaks of COVID-19 before and after the process re-engineering in April and July 2022.Methods: This retrospective cross-sectional study involved 359,845 SARS-CoV-2 RNA specimens with two weeks before and two weeks after the two outbreaks of COVID-19 in April and July. The number, transportation time and detection time of specimens, and the number of reports more than 24 hours were analyzed by SPSS software.Results: 83.16% of people chose oropharyngeal swabs (OPS) specimens to detect SARS-CoV-2 RNA, while 16.84% chose nasopharyngeal swabs (NPS) specimens. There were significant upward trend in the percentage of 10 sample pooling (P-10) from April before process re-engineering to July after process re-engineering (P<0.001). Compared with April, the number of specimens in July increased significantly not only two weeks before but also two weeks after the outbreak of COVID-19, with an increase of 35.46% and 93.94%, respectively. After the process re-engineering, the number of reports more than 24 hours in the two weeks before and after the outbreak of COVID-19 in July was significant lower than that in April before process re-engineering (0% vs 0.06%, and 0 vs 0.89%, both P<0.001).The present study shows that strengthening cooperation of multi-departments in the process re-engineering, especially using P-10 strategy and whole process informatization can improve the detection capability and efficiency of SARS-CoV-2 RNA specimens.